CPC-057 Evolution of Clinical Trial Prescribing Incidents. (12th March 2013) - Larrodé, I; Idoipe, A; Bernabé, S; Pascual, O; Uriarte, M; Real, J
Abstract : Background: It is essential to record incidents in clinical trials (CT) to monitor them appropriately. It is a basic tool to analyse and detect problems. Purpose: To analyse the development in prescription incidents recorded from 2009 to 2011, to identify and resolve quality problems, with the aim of establishing corrective actions to reduce CT problems in a process of continual improvement. Materials and Methods: The most frequent incidents were found in the prescription phase. Data were recorded using the following items: date, person reporting, CT identification, department, professional involved, description of the problem and corrective measures. The evolution of incidents was analysed by chi square. Results: 186 events were recorded in a total of 331 CTs. The most frequent events occurred mainly in the prescription phase (49.0%) followed by dispensing (22.1%), recording (9.6%) and reception (8.6%). The causes of prescribing incidents during 2009, 2010 and 2011 were respectively: no specification that the patient was included in CT (74.2%, 27.1% and 5.3%); incomplete prescription (2.6%, 24.2% and 31.6% ), non-adherence to the study protocol (2.6%, 12.2% and 15.8%), incorrect dose (18%, 18.2% and 36.8%) and other causes (2.6%, 18.2% and 10.5%). The percentage of prescription incidents was: 2.01% (n = 1932) in 2009, 1.64% (n = 2012) in 2010 and 0.92% (n = 2050) in 2011. Prescribing incidents decreased significantly in 2011 compared to previous years. In these cases, there was an immediate intervention with a communication to the investigator. Conclusions: To manage the process as the Ethics Committee requires it is essential to have excellent communication and coordination between the pharmacy department and the other professionals involved. Measures taken were: increased electronic prescribing, using a specific application for CT prescribing and communication to researchers. The measures were effective in achieving a reduction in incidents in CT prescribing. No conflict of interest.